Moisture but not temperature manipulations influence abundance of the free-living larvae of a parasitic nematode infecting Svalbard reindeer - T. M. Moerman; R. Wetherbee; M. Renčo; A. Stien; S. J. Coulson; L. E. Loe (Polar Biology, 2026)
Climate in the Arctic is changing and this may influence parasite-host interactions. Infective free-living larvae of gastrointestinal parasitic nematodes (GIN) are sensitive to environmental conditions. Climate change is thus expected to impact the transmission of these parasites. The encounter between infective larvae and grazing herbivores is likely to depend on vertical distribution of the larvae in soil and vegetation. However, research on the combined effects of temperature and moisture on vertical distribution of GIN larvae is limited. In this full factorial replicated field experiment on Svalbard, we studied the vertical distribution of Ostertagia gruehneri, an important GIN that infects Svalbard reindeer. Larvae were added to experimental plots on the field site and exposed to different temperature and watering conditions. We then tested the prediction that exposure to warmer and drier conditions would result in O. gruehneri larvae moving into the soil, while exposure to cooler and wetter conditions would result in the larvae moving into the vegetation. Five days after the introduction of larvae, we found, as expected, a lower larval abundance in the vegetation under the drier than wetter watering conditions. However, larval abundance in soil was similar under the different watering conditions. We propose larval mortality in the vegetation under the drier water regime as the most probable mechanism explaining these results. Contrary to our expectations, our manipulated temperature increases did not affect abundance in the soil or in vegetation. These results have important implications for understanding parasite availability and transmission into Svalbard reindeer in a changing Arctic.

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

The botanist effect: counties with maximal species richness tend to be home to universities and botanists - Daniel E. Moerman; George F. Estabrook (Journal of Biogeography, 2006)
Aim To investigate the distribution of local flowering plant species richness in areas surrounding American universities. Methods Species richness in university counties was compared with neighbouring counties. Data were derived from Synthesis of the North American Flora ( http://www.phylosystems.com/prepublication ). Probabilities of the resultant distribution were calculated, and the results were also simulated. Results In almost every case there were more species reported in the university county than in its neighbours. Several possible explanations were considered. We conclude that the key element is the presence of botanists in these counties who have, apparently, paid more attention to plants near at hand, and found more species of them there. Main conclusions Ecologists must be aware that numerical data that appear very solid, collected over many decades, may represent not only the qualities of ‘nature’ but also something of the collectors of the data.

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)